Structural, morphological and optical behavior of In1-xHfxP films synthesized via 2, 3-di(tetradecanoyloxy)propyl tetradecanoate assisted sol–gel technique for infrared photodiode applications. (February 2021) - Mahmoud, Waleed E.; Al-Ghamdi, A.A.; Bronstein, Lyudmila M.
Highlights: In1-x Hfx P films were prepared via 2, 3DTPT-assisted sol–gel spin coating method. The Raman spectra confirmed the substitution of Hf dopant in the In cites. The Hf dopant reduced the bandgap and displaced the quantum shoulder to IR-region. The Hf dopant improved the absorbance and photoconductivity of InP films. A photodiode was constructed and showed high response detection for infrared light. Abstract: For the first time, highly crystalline In1-x Hfx P ceramic films (0 ≤ x ≤ 0.09) were synthesized via a sol–gel spin coating technique assisted with 2, 3-di(tetradecanoyloxy)propyl tetradecanoate for the selective detection of infrared light. The impact of the Hf dopant on the structure and topographical characteristics of the InP films was studied using X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), and FTIR spectroscopy. As-synthesized In1-x Hfx P ceramic films possess a cubic structure, in which Hf atoms replace In atoms in the InP crystals. The Raman spectra of In1-x Hfx P ceramic films showed two sharp bands at 302 cm −1 and 344 cm −1 as a result of the first-order TO and LO phonon scattering, whereas two weak bands centered at 649 cm −1 and 691 cm −1 were assigned to the second-order 2TO and 2LO phonon scattering. The XPS spectra revealed that Hf4f occupied the In3d cites in the InP crystals. These films exhibited high optical absorption, good transparency and low reflectance. The inclusion of the Hf dopant in the InP films instigated a decrease of the bandgap from 1.62 eV to 1.44 eV and caused an increase of the optical conductivity and dissipation factor. A photodiode made of the In0.91 Hf0.09 P film was constructed. This photodiode could detect the infrared light with a response time of 1.3 s and a recovery time of 0.9 s. It also exhibited sensitivity of 0.36 mA/W.cm 2 and showed high stability and reproducibility. Therefore, the inclusion of 9 wt% of the Hf dopant in the In cites of the InP crystals may pave the way to the development of highly efficient photodetectors for infrared detection.